(untitled) (International Journal of Built Environment and Sustainability, 2016)
Land title is the designation of an official certificate indicating the name of the individual in whom such ownership is vested. Thus any illegal acquisition of land lacks legal status, then land title regularization will be necessary. When designing and implementing land regularization, the citizen’s opinion is not usually taken into consideration. This study fills this gap by taking statistically representative samples of the opinion of home owners in Ogun State, Nigeria on their level of satisfaction with the latest land regularization policy of Ogun State government. We adopted a purposive sample technique, and we administered a Questionnaire survey to property owners in the study area. Data gathered were analyzed using descriptive method of statistics and the level of satisfaction of the respondents was evaluated based on relevant criteria adopting a 4 point Likert scale. We found that that none of the respondents acquired their through a formal source and none of the have the statutory certificate of occupancy for their land. We also measured the level of satisfaction of the respondents and we found that the property owners dissatisfied with the extent of high-handedness of the staff of the regularization agency and the level of transparency of the scheme. It was also found that home owners mostly dissatisfied with the amount paid for the application and the procedure for processing title documents. It is very important for the government to address dissatisfaction of the citizens with the scheme and to subsequently include sampling opinion of citizen’s level of satisfaction as an integral part of land regularization policies.